Investigating seismicity rates with Coulomb failure stress models caused by pore pressure and thermal stress from operating a well doublet in a generic geothermal reservoir in the Netherlands - Hutka, Gergo András; Cacace, Mauro; Hofmann, Hannes; Mathur, Bakul; Zang, Arno (Netherlands Journal of Geosciences-Geologie En Mijnbouw, 2023)
The utilisation of geothermal energy in the Netherlands is primarily focused on deep sedimentary aquifers, which are often intersected by major faults. Geothermal operations (i.e. fluid production and injection) may alter the effective stress state along these faults and trigger induced seismic events. Pore pressure perturbations have been generally considered the main driver of injection-induced seismicity. However, thermal stresses caused by temperature gradients between the re-injected cold fluid and the reservoir rock may also contribute to the triggering of earthquakes in geothermal reservoirs. While existing geothermal power plants operating in sandstone reservoirs did not produce any major induced seismicity, it is a matter of debate whether a reduction in the temperature of the re-injected fluid could increase the seismic hazard potential. In this study, we applied modified Gutenberg-Richter statistics based on frictional Coulomb stress variations implemented in a coupled thermo-hydro-mechanical model to estimate the seismic hazard caused by the operation of a geothermal doublet. We conducted a systematic parametric study to assess and rank the impact of different intrinsic (geological) and extrinsic (operational) parameters on the induced seismic hazard potential. We identified a competing mechanism between induced variations in pore pressure and thermal stress within the reservoir in controlling induced seismicity. We found that stress changes induced by pore pressure variations are the main cause of seismic hazard, although thermally induced stresses also contribute significantly. The results indicate that by optimising the operational parameters it is possible to increase production efficiency while maintaining a long-term control over the fluid injection-induced seismicity.
CRIS-Team Scopus Importer:2023-07-21
Keywords: deep geothermal energy; Gutenberg-Richter statistics; hazard assessment; induced seismicity; Mohr-Coulomb failure approach; thermal stresses